The Message behind the Syntax “There is no god but Allah, Muhammad is the Messenger of Allah” : A Study and Investigation (Islamic Sciences Journal, 2024)
ABSTRACT The library holds a varied assortment of books and treatises covering multiple areas of expertise. The ancients manually transcribed and curated knowledge, dedicating their lives to facilitating its accessibility for students and scholars. One text provides a summary of knowledge rulings. The researcher was motivated by their heritage and a desire for pride, leading them to consciously choose to study and investigate methods for documenting the subject matter. Through perseverance, the researcher was able to obtain a valuable manuscript. The researcher determined that the interdisciplinary research is a valuable addition to the field after careful review. Thus, it suggests researching, validating, and sharing it with experts in the field. The study was titled "Syntax of There is no god but God, and Muhammad is the Messenger of Allah." Upon obtaining a manuscript inscribed with the declaration "There is no god but Allah, and Muhammad is the Messenger of Allah" in Arabic, the researcher felt compelled to examine its contents. The manuscript discusses the significance of monotheism in Islam.
Keywords: Fanari, Sibawayh, there is no god but God, the exception, raised and erected.